PROBLEMS IN WORD LEARNING FOR ENGLISH LANGUAGE STUDENTS AND THEIR SOLUTIONS ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
English proficiency is determined by the vocabulary of foreign language learners as well as native speakers. While expanding one's vocabulary is important, it also presents various challenges, especially for non-native English students. Students with low vocabulary do not achieve satisfactory academic results in several university-level courses related to language skills, linguistics, literature, and translation. This article specifically aims to explore the problems encountered in learning English and suggests some vocabulary learning strategies to minimize potential problems.